Injury Patterns in Pediatric Facial Fractures Unique to an Urban Environment - Sclafani, Anthony P.; Sclafani, Matthew Scott; Long, Sallie; Losenegger, Tasher; Spielman, Daniel; Obayemi, Ade; Cosiano, Michael F.; Neuner, Romy; Kacker, Ashutosh; Reeve, Gwendolyn; Stewart, Michael G. (Facial Plastic Surgery, 2021)
This study aimed to define better the clinical presentation, fracture patterns, and features predictive of associated injuries and need for surgery in pediatric facial trauma patients in an urban setting. Charts of patients 18 years or younger with International Classification of Disease 9th and 10th revision (ICD-9/ICD-10) codes specific for facial fractures (excluding isolated nasal fractures) at NY-Presbyterian/Weill Cornell Medical Center between 2008 and 2017 were retrospectively reviewed. Of 204 patients, most were referred to the emergency department by a physician's office or self-presented. Children (age 0–6 years) were most likely to have been injured by falls, while more patients 7 to 12 years and 13 to 18 years were injured during sporting activities (p < 0.0001). Roughly half (50.5%) of the patients had a single fracture, and the likelihood of surgery increased with greater numbers of fractures. Older patients with either orbital or mandibular fractures were more likely to undergo surgery than younger ones (p = 0.0048 and p = 0.0053, respectively). Cranial bone fractures, CSF leaks, and intracranial injuries were more common in younger patients (p < 0.0001) than older patients and were more likely after high energy injuries; however, 16.2% of patients sustaining low energy injuries also sustained cranial bone, CSF leak, or intracranial injury. In an urban environment, significant pediatric facial fractures and associated injuries may occur after nonclassic low kinetic energy traumatic events. The age of the patient impacts both the injuries sustained and the treatment rendered. It is essential to maintain a high index of suspicion for associated injuries in all pediatric facial trauma patients.
Keywords: pediatric facial fracture; frontal sinus fracture; maxilla fracture; zygoma fracture; orbital fracture